Stronger together: work engagement and emotional intelligence abilities and their interactive effect on personal and work attitudes in teachers - Mérida-López, Sergio; Sánchez-Álvarez, Nicolás; Quintana-Orts, Cirenia Luz; Extremera-Pacheco, Natalio; Rey-Peña, Lourdes (My University, 2019)
In this study, we investigated the associations between work engagement and personal (happiness and life satisfaction) and organizational (job satisfaction) work attitudes in teachers and the interactive role of emotional intelligence abilities in this link. Two hundred and twenty secondary teachers (129 females) participated and moderation analyses were performed. The results showed that work engagement was positively related to both happiness and life and job satisfaction. Emotion regulation was the only dimension which was significantly associated with both personal and work attitudes. Thus, emotion regulation moderated the relationships betweenwork engagement and personal and work outcomes. The analysis revealed that teachers who reported higher emotion regulation and higher engagement were more likely to report higher levels of both personal and work attitudes. Our findings suggest that organizational managers could develop emotion regulation abilities and increase employee engagement as a way of promoting more positive work attitudes and well-being among teachers.
Keywords: Inteligencia emocional; Work engagement; Emotional intelligence; Work attitudes; Teachers